2020
DOI: 10.2147/eb.s247121
|View full text |Cite
|
Sign up to set email alerts
|

<p>Neuro-Ophthalmological Manifestations of Obstructive Sleep Apnea: Current Perspectives</p>

Abstract: Obstructive sleep apnea (OSA) is a disease of obstructed airways during sleep that significantly impacts the quality of life and increases the risk of various systemic diseases. OSA has been studied as a risk factor for a number of neuro-ophthalmic conditions and a strong relationship has been established with non-arteritic anterior ischemic optic neuropathy (NAION). The incidence of glaucoma and stroke have also been significantly associated with OSA and are conditions that may also be seen by neuro-ophthalmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 74 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…In adults, OSA increases the risk of glaucoma, ischemic optic neuropathy [25,26], and floppy eyelid syndrome [17,27]. "Self-reported snoring" is associated with reduced retinal thickness and vascular density [28].…”
Section: Discussionmentioning
confidence: 99%
“…In adults, OSA increases the risk of glaucoma, ischemic optic neuropathy [25,26], and floppy eyelid syndrome [17,27]. "Self-reported snoring" is associated with reduced retinal thickness and vascular density [28].…”
Section: Discussionmentioning
confidence: 99%
“…Sleep apnea can be associated with floppy eyelid syndrome [76] and it behooves the VCP to evaluate patients for this condition because it can cause irritated eyes or even cornea abrasions during sleep. Notably, an association between sleep apnea and intracranial hypertension has been suggested; although the relationship between these two conditions may not be sufficient to recommend fundus examinations on every patient with sleep apnea [77], it seems reasonable for VCPs to look for papilledema in all of their sleep apnea patients.…”
Section: Respiratorymentioning
confidence: 99%
“…Previous studies showed an association of OSA with an increased risk of cardiovascular and cerebrovascular diseases, stroke, coronary artery disease, diabetes, hypercholesterolemia and hypertension [ 5 , 6 , 7 , 8 ]. Furthermore, OSA has been shown to be a major risk factor concerning optic nerve disorders, such as glaucoma, non-arteritic anterior ischemic optic neuropathy, central serous chorioretinopathy, papilledema and retinal vein occlusion [ 9 , 10 , 11 ]. The term “glaucoma” describes a collection of progressive, chronic optic neuropathies resulting from the degeneration of retinal ganglion cells and leading to visual impairment.…”
Section: Introductionmentioning
confidence: 99%